Ahmad Dahlan Thoughts Through Al-Ma'un and Higher Order Thinking Skill (HOTS) in Education: Is It Relevance? - Ahmad Amin Agustiar; Nur Amalia (Jurnal Muhammadiyah Studies, 2024)
This research seeks to determine the significance of Higher-Order Thinking Skills (HOTS) learning in the Al-Ma'un philosophy, as KH Ahmad Dahlan taught. The method employed is a literature review, with data collected from literature relevant to the theme of KH Ahmad Dahlan and Higher-Order Thinking Skills (HOTS) learning. The data is then analyzed thematically and processed using an inductive method. According to the findings, KH Ahmad Dahlan taught Al-Ma'un to his students, which is similar to Higher-Order Thinking Skills or HOTS nowadays.